Menyulam Etika dan Kemanusiaan: Tafsir Inklusif Nurcholish Madjid Tentang Islam dan Pluralitas di Indonesia (1970-2004) - Andoni, Yudhi; Yulia, Novi (Analisis Sejarah, 2025)
This research examines the inclusive understanding of Islam and pluralism proposed by Nurcholish Madjid in the socio-political context of Indonesia from 1970 to 2004. It aims to investigate how Madjid’s ideas helped reframe the relationship between Islamic ethics and the state during the New Order regime and the Reformasi era. Employing a critical historical approach—comprising source collection, criticism, interpretation, and historiography—the inquiry primarily draws on Madjid’s works and related secondary literature. The conclusion identifies that Madjid believed in a modern, inclusive, and humanistic Islam based on universal values and contextual theology. He argued that Islam serves as a foundation for ethics, rather than a political philosophy, and envisioned it aligning with Pancasila and democratic ideals. The research concludes that Madjid’s thought provides critical contribution that balances faith, humanism, and national identity in a pluralistic nation.